The role of participants in education research : ethics, epistemologies, and methods - Midgley, Warren; Danaher, Patrick Alan, 1959-; Baguley, Margaret, 1966- (New York : Routledge, 2013)
"This book explores different perspectives on the role, influence and importance of participants in education research. Drawing on a variety of philosophical, theoretical and methodological approaches, the book examines how researchers relate to and with their participants before, during, and after the collection and/or production of data; reimagining the rights of participants, the role/s of participants, the concept/s of "participant" itself"--
pt. I. Ethics -- pt. II. Epistemologies -- pt. III. Methods.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Education -- Research; Electronic books